2020
DOI: 10.1177/1120672120904670
|View full text |Cite
|
Sign up to set email alerts
|

The significance of pigment epithelial detachment in central serous chorioretinopathy

Abstract: Purpose: To investigate the significance of the presence and form of pigment epithelial detachment in the course of central serous chorioretinopathy as well as corticosteroid use as a risk in our patient cohort. Material and methods: Retrospective, single center study of central serous chorioretinopathy patients between January 2013 and January 2019 recording corticosteroid use prior to onset and presence and type of pigment epithelial detachment (flat-irregular, dome-shaped, none) in relationship to disease c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In addition, shallow irregular PED areas were highlighted on the heatmaps. A small, flat, irregular PED could be a marker of chronic or recurrent CSC and implies genetic overlap of patients with AMD, which can explain the refractoriness of the condition 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, shallow irregular PED areas were highlighted on the heatmaps. A small, flat, irregular PED could be a marker of chronic or recurrent CSC and implies genetic overlap of patients with AMD, which can explain the refractoriness of the condition 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…As clinical research advances, our understanding of CSC has developed from the RPE level to the choroidal level. It is now generally accepted that the pathogenesis of CSC is associated with choroidal vascular hyperpermeability, RPE barrier disruption, and choroidal dysfunction [15,16]. In FFA examinations, we observed RPE barrier disruption and fluorescein leakage.…”
Section: Discussionmentioning
confidence: 54%
“…CSC after the use of exogenous glucocorticoids has been widely reported in the literature, including oral, inhaled, intranasal, intravenous, intramuscular, intraarticular, and periocular administrations, etc. [ 2 , 5 , 12 15 ]. Prakash et al have reported a case where a 35-year-old male experienced four recurrent episodes of CSC within one year, a few days before each episode he was using dexamethasone eye drops intranasally for rhinitis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%